Reevaluating Glioma Outcomes in Low- and Middle-Income Countries: A Retrospective Study of 53 Patients Using WHO CNS Tumor Classification 2021 at CN Center, Gauhati Medical College, India - Saikia, Amrit Kumar; Kumar Baishya, Basanta; Bhattacharyya, Angirash; Bhuyan, Mrinal (Journal of Neonatal Surgery, 2025)
Background: The 2021 WHO Classification of Central Nervous System (CNS) tumors introduced molecular markers that significantly impact glioma diagnosis and treatment. However, challenges persist in low- and middle-income countries (LMICs), where resource constraints affect the implementation of advanced diagnostics and therapeutic strategies. This study retrospectively analyzes 53 glioma patients operated at CN Center, Gauhati Medical College from January 2022 to May 2023, incorporating the WHO 2021 classification framework. Methods: A retrospective cohort study of 53 glioma patients was conducted. Histopathological and molecular marker-based classification was performed using WHO 2021 guidelines. Treatment modalities, including surgery, radiotherapy, and chemotherapy, were analyzed in relation to survival outcomes. Statistical analysis included Kaplan-Meier survival curves and Cox proportional hazard models. Results: Of 53 cases, glioblastoma (GBM) was the most prevalent (47.2%), followed by IDH-mutant astrocytomas (22.6%) and oligodendrogliomas (15.1%). MGMT promoter methylation was found in 38% of GBM cases, correlating with improved progression-free survival (PFS). The median overall survival (OS) was 14.3 months for GBM, 42.1 months for IDH-mutant astrocytomas, and 58.7 months for oligodendrogliomas. A significant disparity in access to molecular diagnostics and adjuvant therapies was noted in LMIC settings. Conclusion: Despite advancements in glioma classification, LMICs face barriers in adopting molecular diagnostics, impacting treatment stratification and survival outcomes. The findings highlight the urgent need for cost-effective solutions and improved healthcare infrastructure to optimize glioma management.